Preparação de ferro metálico suportado em polietileno para uso como catalisador flutuante na reação foto-fenton - Mossmann, Anelise (2019)
In the present paper, zero-valent iron particles were supported on low density polyethylene. The material produced was used as a buoyant catalyst in the removal of the Ponceau 4R azo dye from an aqueous solution via heterogeneous Photo-Fenton reaction. The catalyst material was characterized by X-ray diffraction (XRD), scanning electron microscopy (SEM) coupled to X-ray dispersive energy (EDS) spectroscopy, Fourier transform infrared spectroscopy (FTIR) and photographic images. In the study were analyzed different process variables, such as pH, concentration of hydrogen peroxide and dye. The results showed excellent adhesion of zero valence iron to the polyethylene pellet’s surface. The buoyant catalyst presented satisfactory catalytic activity, reaching total discoloration of the dye in 15 min of reaction. It was also observed that the hydroxyl radical (∙OH) and singlet oxygen (1O2) were dominant in the reaction. Other advantages of the buoyant catalyst, such as easy separation of the aqueous solution, good stability and possibility of reuse are also highlighted, since the dye removal efficiency remained high after four successive cycles of use. In general, this research demonstrated how efficient the use of zero-valent iron in photo-Fenton reactions is, and that the proposed buoyant catalyst of this research can be estimated as a potential alternative for application in environmental remediation.